The Influence of Social Support and Health on Everyday Problem Solving in Adult African Americans - Whitfield, Keith E.; Wiggins, Sebrina (Experimental aging research, 2003)
The purpose of this study was to examine the relationship between social support, health status, and everyday problem solving in African Americans. The sample included subjects recruited from Baltimore, Maryland. The sample consisted of 249 community-dwelling African American adults, 32% of whom were male, with a sample mean age of 67.8 years ( SD =8.47 years). Variables included: Everyday Problem Solving Test (EPT), social support given and received, physical limitations, counts of chronic illness, smoking, and demographic information. Using stepwise regression, age, education, physical limitations, and social support given were found to be significant predictors of performance on the EPT. Further analysis found support for a partial mediating effect of physical limitations on the relationship between social support and everyday problem solving. The results indicate that there may be differences in the cognitive abilities of those actively involved in social activities.